Financial Implications of Intravenous Anesthetic Drug Wastage in Operation Room - Kaniyil, Suvarna (Anesth Essays Res, 2017)
BACKGROUND AND OBJECTIVES: Anesthetic drugs and material wastage are common in operation rooms (ORs). In this era of escalating health-care expenditure, cost reduction strategies are highly relevant. The aim of this study was to assess the amount of daily intravenous anesthetic drug wastage from major ORs and to estimate its financial burden. Any preventive measures to minimize drug wastage are also looked for. METHODS: It was a prospective study conducted at the major ORs of a tertiary care hospital after getting the Institutional Research Committee approval. The total amount of all drugs wasted at the end of a surgical day from each major OR was audited for five nonconsecutive weeks. Drug wasted includes the drugs leftover in the syringes unutilized and opened vials/ampoules. The total cost of the wasted drugs and average daily loss were estimated. RESULTS: The drugs wasted in large quantities included propofol, thiopentone sodium, vecuronium, mephentermine, lignocaine, midazolam, atropine, succinylcholine, and atracurium in that order. The total cost of the wasted drugs during the study period was Rs. 59,631.49, and the average daily loss was Rs. 1987.67. The average daily cost of wasted drug was maximum for vecuronium (Rs. 699.93) followed by propofol (Rs. 662.26). INTERPRETATION AND CONCLUSIONS: Financial implications of anesthetic drug wastage can be significant. Propofol and vecuronium contributed maximum to the financial burden. Suggestions for preventive measures to minimize the wastage include education of staff and residents about the cost of drugs, emphasizing on the judicial use of costly drugs.